Detection of Planktothrix rubescens (Cyanobacteria) associated with microcystin production in a freshwater reservoir - Paulino, Sérgio (2012)
So far, the presence of microcystins in Portuguese freshwater resources has always been attributed to the bloom-forming cyanobacteria Microcystis aeruginosa. In 2005, however, microcystins were detected at the Beliche reservoir (Algarve, South Portugal), following the development of a bloom dominated by Planktothrix rubescens. The identity of the causative organism was confirmed by combining both morphological and 16S rRNA gene sequence analysis. Its ability to produce microcystins was confirmed by HPLC and MALDI-TOF MS. Unlike M. aeruginosa that usually accumulates near the water surface, P. rubescens found at the Beliche reservoir accumulated only at deep water levels. Being invisible from the surface, the occurrence of toxic P. rubescens in freshwater resources requires special attention when designing site inspection and sampling procedures for the correct risk assessment and management of cyanobacterial blooms in the field.